2010
DOI: 10.4103/1319-3767.65194
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous colorectal polyps in patients referred for colonoscopy in a regional hospital in Kuwait

Abstract: Background/Aim:Adenomatous colorectal polyps (ACPs) are known to be the precursor lesions for colorectal cancer. The aim of the study was to determine the prevalence, endoscopic and pathological features of ACPs in patients referred for colonoscopy.Patients and Methods:The endoscopic and histological reports of adult patients who underwent complete colonoscopy in the gastroenterology unit of a regional Kuwaiti hospital between January 2008 and December 2008 were retrospectively studied. The specimens of polyps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
(32 reference statements)
3
13
0
Order By: Relevance
“…In the recent literature of colorectal polyps from the region and Asia, Al-Rashed and Al-Amri (1996) from KSA (Bafandah et al, 2005; from Iran have reported minimum age results of about 42 years, with wide standard deviations. From Kuwait a very close figure of 45 years has been quoted (Al-Enezi et al, 2010). On the other side of spectrum; mean age has been reported as above 50 years (Wisedopas et al, 2005;Tony et al, 2007), reaching up to maximum of 58 years (Bafandeh et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In the recent literature of colorectal polyps from the region and Asia, Al-Rashed and Al-Amri (1996) from KSA (Bafandah et al, 2005; from Iran have reported minimum age results of about 42 years, with wide standard deviations. From Kuwait a very close figure of 45 years has been quoted (Al-Enezi et al, 2010). On the other side of spectrum; mean age has been reported as above 50 years (Wisedopas et al, 2005;Tony et al, 2007), reaching up to maximum of 58 years (Bafandeh et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…From Iran 78.9% adnomatous polypswere reported (Zahir et al, 2010). From Kuwait one group report that out of 530 eligible patients, 10% had 103 adenomatous polyps (Al-Enezi et al, 2010) and finally Al-Rashed and Al-Amri (1996) from KSA in their 2772 colonoscopy study, reported 188 polyps, most of them (89.5%) were tubular and tubulovillous adenomas. In contrast to all these consistent results, only one study from Thailand report higher frequency of Hyperplastic polyps (39%), followed by 36% tubular adenoma (Wisedopas et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, this ratio was reported to be about 2:1 in countries such as Kuwait (Al-Enezi et al, 2010) and Saudi Arabia (Albasri et al, 2014). Also, Hajmanoochehri et al, 2014 reported an M/F ratio of 1.03:1 for colon adenocarcinoma.…”
Section: Discussionmentioning
confidence: 97%